2023
DOI: 10.7185/geochemlet.2307
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between clay minerals and organics in asteroid Ryugu

Abstract: The Hayabusa 2 spacecraft brought back to Earth grains of the carbonaceous asteroid Ryugu. Such grains represent the pristine state of CI chondritic materials and have been preserved from exposure to Earth's atmosphere. Here, we show evidence of the presence of organics trapped within the interlayer space of smectite layers in Ryugu grains. No such organics are found in the Orgueil CI meteorite. We put forward that the organics within the interlayer space of smectite in Orgueil CI meteorite were lost during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…It is not clear whether the organic IR features are derived from macromolecular organic matter or smaller/soluble organic compounds. However, one possibility is that the organics overlapping with phyllosilicates could be soluble compounds present in the interlayer spaces; additionally, organics that did not overlap with phyllosilicates could be macromolecular materials, since the organic matter is known to be present in the interlayer spaces of phyllosilicates in Ryugu particles (Viennet et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear whether the organic IR features are derived from macromolecular organic matter or smaller/soluble organic compounds. However, one possibility is that the organics overlapping with phyllosilicates could be soluble compounds present in the interlayer spaces; additionally, organics that did not overlap with phyllosilicates could be macromolecular materials, since the organic matter is known to be present in the interlayer spaces of phyllosilicates in Ryugu particles (Viennet et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Looking at the distribution of the diffuse organic matter in the whole-rock sample, the CH X signature of these labile molecules seems intimately linked to the phyllosilicates. Viennet et al (2023) have suggested that organics are contained in the interlayer space of Ryugu smectites, whereas the interlayer space of Orgueil A198, page 7 of 14 Fig. 6.…”
Section: Insoluble Organic Matter Analysismentioning
confidence: 99%
“…Therefore, the iron nitride could have been produced by vapour from Ryugu's materials that is richer in nitrogen than carbon. It has been suggested that NH-rich compounds and NH-bearing organics occur within the interlayers of phyllosilicates in Ryugu samples 37,38 , but a large clump of nitrogen-dominated…”
Section: Nitridation Of the Space-weathered Surfacesmentioning
confidence: 99%
“…37 CAS Center for Excellence in Deep Earth Science, Guangzhou, China. 38 Japan Synchrotron Radiation Research Institute, Sayō, Japan. 39 University of Chinese Academy of Sciences, Beijing, China.…”
Section: Helium Ion Irradiation Experiments Of Ryugu Grainsmentioning
confidence: 99%